A methodological proposal to benefit from team knowledge: an experience in a Mexican SME dedicated to the design of electromechanical devices. Issue 3 (8th August 2016) - Perez-Soltero, Alonso; Galvez-Leon, Humberto; Barcelo-Valenzuela, Mario; Sanchez-Schmitz, Gerardo
Abstract : Purpose: This study aims to propose a methodology in order to develop an organizational memory to benefit from team knowledge and to make the design of electromechanical devices processes more efficient. Design/methodology/approach: Different frameworks and methods were analyzed from literature, obtaining key ideas to be included in the methodology developed and considering other approaches to apply in team knowledge about design processes. The research was conducted as a case study in a Mexican SME dedicated to the manufacturing and installation of electromechanical devices where the methodology was implemented. Findings: A five-stage methodology was developed which consisted of preparation, identification, capture & storage, dissemination & application, and finally the evaluation & feedback stage. An implementation of the described processes was carried out, which was materialized into a technological tool that represents the organizational memory where knowledge was captured, organized and disseminated. Practical implications: This study offers guidelines that can be applied in other organizations where team knowledge on design processes have not been adequately used for company´s improvement. The application of this methodology could be a strategy that enabled team knowledge to store their experience. This knowledge could then be consulted and recovered by the workgroup in an effective manner to solve new problems. Originality/value: A methodological proposal to develop an organizational memory about team knowledge was developed. In order to evaluate the impact of the methodology implementation, a variety of indicators were proposed, which were classified as economic, organizational and performance indicators.